Immune Activations and Viral Tissue Compartmentalization During Progressive HIV-1 Infection of Humanized Mice - Su, Hang; Cheng, Yan; Sravanam, Sruthi; Mathews, Saumi; Gorantla, Santhi; Poluektova, Larisa Y.; Dash, Prasanta K.; Gendelman, Howard E. (Frontiers in Immunology, 2019)
Human immunodeficiency virus type one (HIV-1) tissue compartments are established soon after viral infection. However, the timing in which virus gains a permanent foothold in tissue and the cellular factors that control early viral-immune events are incompletely understood. These are critical events in studies of HIV-1 pathogenesis and in the development of viral reservoirs after antiretroviral therapy. Moreover, factors affecting the permanence of viral-tissue interactions underlie barriers designed to eliminate HIV-1 infection. To this end we investigated the temporal and spatial viral and host factors during HIV-1 seeding of tissue compartments. Two humanized NOD.Cg-Prkdcscid IL2rgtm1Wjl/SzJ mouse models were employed. In the first, immune deficient mice were reconstituted with human CD34+ cord blood hematopoietic stem cells (HSC) (hu-HSC) and in the second mice were transplanted with adult mature human peripheral lymphocytes (hu-PBL). Both, in measure, reflect relationships between immune activation and viral infection as seen in an infected human host. Following humanization both mice models were infected with HIV-1ADA at 104 50% tissue culture infective doses. Viral nucleic acids and protein and immune cells profiles were assayed in brain, lung, spleen, liver, kidney, lymph nodes, bone marrow and gut from 3 to 42 days. In hu-HSC and PBL mice HIV-1 was readily detected in all tissues by day 14 and 3, respectively. T cell maturation and inflammation factors were linked to differences in viral tissue seeding in hu- HSC and PBL mice. We conclude that early viral tissue compartmentalization provides a roadmap for investigations into HIV-1 elimination.